Building food safety into the company culture: a look at Maple Leaf Foods. (July 2014) - Jespersen, Lone; Huffman, Randy
Maple Leaf Foods learned a hard lesson following its tragic 2008 Listeria outbreak that ended up taking the lives of 23 Canadians. The organization has since 2008 transformed its commitment to food safety with a strong drive and manifest in embedding sustainable food safety behaviours into the existing company culture. Its focus on combining technical risk analysis with behavioural sciences has led to the development and deployment of a food safety strategy deeply rooted in the company values and management commitment. Using five tactics described in this article the organization has been on a journey towards food safety transformation through adoption of best practices for people and systems. The approach to food safety has been one where food safety is treated as a non-competitive issue and Maple Leaf Foods have been open to sharing learning about what happened and how the organization will continue to take a leadership position in food safety to continuously raise the bar for food safety across the industry. Maple Leaf Foods has benefited tremendously by learning about best practice from numerous companies in North America and around the world. The authors believe this brief story will bring value to others as we continue to learn and improve.